2019
DOI: 10.1080/02678292.2019.1641638
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-linked cyanobiphenyl-based liquid crystal dimers and the twist-bend nematic phase

Abstract: The synthesis and characterisation of two series of cyanobiphenyl-based liquid crystal dimers containing sulfur links between the spacer and mesogenic units, the 4',4''-[1,ωalkanediylbis(thio)]bis-[1,1'-biphenyl]-4-carbonitriles (CBSnSCB), and 4'-({ω-[(4'cyano[1,1'-biphenyl]-4-yl)oxy]alkyl}thio)[1,1'-biphenyl]-4-carbonitriles (CBSnOCB), are described. The odd members of both series show twist-bend nematic and nematic phases whereas the even members exhibit only the nematic phase. An analogous cyanoterphenylbas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 58 publications
8
51
0
Order By: Relevance
“…Recently, Cruickshank et al. likewise reported CBS n SCB and CBS n OCB . To the best of our knowledge, all solely chalcogen‐linked twist–bend nematogens developed so far are based on phenyl rings as the π‐conjugated moieties in the mesogenic arms; other π‐conjugated cores have never been addressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Cruickshank et al. likewise reported CBS n SCB and CBS n OCB . To the best of our knowledge, all solely chalcogen‐linked twist–bend nematogens developed so far are based on phenyl rings as the π‐conjugated moieties in the mesogenic arms; other π‐conjugated cores have never been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…[58] Recently, Cruickshank et al likewise reported CBSnSCB and CBSnOCB. [59] To the best of our knowledge,a ll solely chalcogen-linked twist-bend nematogens developed so far are based on phenyl rings as the p-conjugatedm oieties in the mesogenic arms; other p-conjugatedc ores have never been addressed. In addition, molecular bendingr esulting from the different chalcogen linkagesa nd the symmetry of mesogenic arm structures have yet to be analyzed systematicallyt ou nderstand the necessary molecular design features to obtain twist-bend nematics.…”
Section: Introductionmentioning
confidence: 99%
“…[38] In this work, the materials studied feature am ethylene spacer with varying linking group;i ti st herefore to be expected that as linkersa re used which introduce greater flexibility (increased FWHM) the average bend angle decreases further away from the tetrahedral angle imposed by the methylene spacer.A3D plot of scaled transition temperature versus FWHM versus average bend shows how these three properties are related ( Figure 3c). Clearly, both averageb enda nd flexibility play ap art in dictating the scaled transition temperature and this can explain the previously unexpectedly low values of dT of materials such as CBS3SCB [27,39] and CBO5OCB, [24,40] both of which satisfy the angular dependency of the N TB phase but are highlyf lexible. Furthers tudies into the relationship between molecular bend and the incidence of the N TB phase will be expected to be complicated by the difficulty in preparing spacers which give bend angles larger than those presented here without introducing flexibility (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…independently reported the synthesis and transition temperatures of these two materials, [39] in this work we chose to use transition temperatures for compounds 6 and 7 reportedb yA rakawa et al [27] because the clearing points are marginally higher. independently reported the synthesis and transition temperatures of these two materials, [39] in this work we chose to use transition temperatures for compounds 6 and 7 reportedb yA rakawa et al [27] because the clearing points are marginally higher.…”
Section: Addendummentioning
confidence: 99%
“…From a chemist's perspective, understanding the molecular features influencing the formation and stabilisation of the N TB phase is of paramount importance, and allows for the design of new materials that have targeted properties. These studies have involved systematically varying the molecular structure of twist-bend nematogens and have included varying the spacer length [11,12], the nature of the link between the spacer and mesogenic groups [13][14][15][16][17], the structure of the mesogenic units [18,19], and of the terminal substituents [12,[20][21][22][23]. By far the greatest number of twist-bend nematogens reported so far may be described as odd-membered liquid crystal dimers having a similar molecular curvature to CB7CB.…”
Section: Introductionmentioning
confidence: 99%